Impact on life expectancy of HIV-1 positive individuals of CD4+ cell count and viral load response to antiretroviral therapy - May, Margaret T; Gompels, Mark; Delpech, Valerie; Porter, Kholoud; Orkin, Chloe; Kegg, Stephen; Hay, Phillip; Johnson, Margaret; Palfreeman, Adrian; Gilson, Richard; Chadwick, David; Martin, Fabiola; et al. (AIDS (London), 2014)
The objective of this study is to estimate life expectancies of HIV-positive patients conditional on response to antiretroviral therapy (ART). Patients aged more than 20 years who started ART during 2000-2010 (excluding IDU) in HIV clinics contributing to the UK CHIC Study were followed for mortality until 2012. We determined the latest CD4 cell count and viral load before ART and in each of years 1-5 of ART. For each duration of ART, life tables based on estimated mortality rates by sex, age, latest CD4 cell count and viral suppression (HIV-1 RNA <400 copies/ml), were used to estimate expected age at death for ages 20-85 years. Of 21 388 patients who started ART, 961 (4.5%) died during 110 697 person-years. At start of ART, expected age at death [95% confidence interval (CI)] of 35-year-old men with CD4 cell count less than 200, 200-349, at least 350 cells/μl was 71 (68-73), 78 (74-82) and 77 (72-81) years, respectively, compared with 78 years for men in the general UK population. Thirty-five-year-old men who increased their CD4 cell count in the first year of ART from less than 200 to 200-349 or at least 350 cells/μl and achieved viral suppression gained 7 and 10 years, respectively. After 5 years on ART, expected age at death of 35-year-old men varied from 54 (48-61) (CD4 cell count <200 cells/μl and no viral suppression) to 80 (76-83) years (CD4 cell count ≥350 cells/μl and viral suppression). Successfully treated HIV-positive individuals have a normal life expectancy. Patients who started ART with a low CD4 cell count significantly improve their life expectancy if they have a good CD4 cell count response and undetectable viral load.